Examining the Experiences of Small, Independent Grocers during the COVID-19 Pandemic - Picardy, Jamie; Luken, Lisa; Michaud, Iris; Lefebvre, Martha (Maine Policy Review, 2022)
The COVID-19 pandemic has exposed existing vulnerabilities across various sectors of the economy and society. Disruptions to the food chain have been common during the pandemic, resulting in empty shelves at grocery stores and modifications to consumer culture. Within this study, we examined resilience (characterized by flexibility, diversity, redundancy, adaptability, innovation, self-reliance and infrastructure) of small, independent grocery stores in Maine.
Keywords: Resilience; Cooperation; Network; Local and Regional Food System; COVID-19